Erratum: LUCAS SILVEIRA ANTONIETTO, CLÁUDIA PINTO MACHADO, DERMEVAL APARECIDO DO CARMO & JOSÉ WILSON CORREA ROSA (2012) Recent Ostracoda (Arthropoda, Crustacea) from São Pedro-São Paulo Archipelago, Brazil: a preliminary approach. Zootaxa, 3335, 29–53. - Antonietto, Lucas Silveira; Machado, Cláudia Pinto; Do Carmo, Dermeval Aparecido; Rosa, José Wilson Correa (Zootaxa, 2012)
(Erratum)